Narrativas travestis e transexuais: transbordar resistências - Santos Sobrinho, Paulo Ribeiro dos (2018)
This research compiled some narratives aiming infant histories, scholar trajectory and prostitution of transgender and transvestite people. The methodological procedure used to reach this objective was the exploratory research using a focal group to data search (performed in 2016) and individual interviews (performed in 2017). The data were transcripted and analyzed by trans-authors as Lanz (2014), Andrade (2015), Reidel (2011), using categories such as infanthood, education, sexuality, and prostitution. The outcomes suggest that the school still is an exclusion and rejection space, where the binaries stereotypes are predominant. However, the speech also demonstrated that are gaps which put forward and potentialize all these trajectories, putting in movement these body types. Keywords: Transsexuality. Travesty. Childhood. Education. Prostitution.